( x 2 − x − 2 ) ( x 2 − 2 x − 3 ) ( x 2 − 3 x − 4 ) ( x 2 − 4 x − 5 ) ( x 2 − 5 x − 6 ) ( x 2 − 6 x − 7 ) ( x 2 − 3 x + 2 ) ( x 2 − 4 x + 3 ) ( x 2 − 5 x + 4 ) ( x 2 − 6 x + 5 ) ( x 2 − 7 x + 6 ) ( x 2 − 8 x + 7 )
Find the value of this expression when x = − 3 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Lol!! Writing color latex once in a non-nlack colour for the cancek latex and then switching to black color is a hilarious job. (+1) for taking up the hard work!!!
Log in to reply
Haha thanks. It looks neater this way, but the number of braces! Though I'd say it's good training for me, since I'm pursuing a computer science degree.
You should see the number of colors I used here (Do try the question first)
@Hung Woei Neoh Wow!!! Did you notice that coincidentally, only 64% of people got the question correct!!!
To be less specific, let's consider these expressions : N ( x , n ) = x 2 − ( n + 1 ) x + n and D ( x , n ) = x 2 − ( n − 1 ) x − n
We can easily compute that : N ( x , n ) = ( x − 1 ) ( x − n ) and D ( x , n ) = ( x + 1 ) ( x − n )
Therefore, D ( x , n ) N ( x , n ) = x + 1 x − 1
The first expression can be rewritten as : ∏ n = 2 7 D ( x , n ) N ( x , n ) = ( x + 1 x − 1 ) 6
To answer the very first question, yes it is easier to simplify it :)
Substitute x = − 3 then you get :
∏ n = 2 7 D ( − 3 , n ) N ( − 3 , n ) = ( − 2 − 4 ) 6 = 2 6 = 6 4
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Multiplying and Dividing Monomials
( x 2 − x − 2 ) ( x 2 − 2 x − 3 ) ( x 2 − 3 x − 4 ) ( x 2 − 4 x − 5 ) ( x 2 − 5 x − 6 ) ( x 2 − 6 x − 7 ) ( x 2 − 3 x + 2 ) ( x 2 − 4 x + 3 ) ( x 2 − 5 x + 4 ) ( x 2 − 6 x + 5 ) ( x 2 − 7 x + 6 ) ( x 2 − 8 x + 7 ) = ( x − 2 ) ( x + 1 ) ( x − 3 ) ( x + 1 ) ( x − 4 ) ( x + 1 ) ( x − 5 ) ( x + 1 ) ( x − 6 ) ( x + 1 ) ( x − 7 ) ( x + 1 ) ( x − 2 ) ( x − 1 ) ( x − 3 ) ( x − 1 ) ( x − 4 ) ( x − 1 ) ( x − 5 ) ( x − 1 ) ( x − 6 ) ( x − 1 ) ( x − 7 ) ( x − 1 ) = ( x + 1 ) 6 ( x − 1 ) 6
Substitute x = − 3 into the expression:
( − 3 + 1 ) 6 ( − 3 − 1 ) 6 = ( − 2 ) 6 ( − 4 ) 6 = 2 6 2 1 2 = 2 6 = 6 4